Post-COVID-19 fungal rhinosinusitis – Correlation between histopathological and microbiological findings - Chaithra K,; Preeta Naik,; Purushotham R,; Nagesha KR, (Asian Journal of Medical Sciences, 2023)
Background: COVID-19 was a global pandemic. In the late December 2019, several patients presented with symptoms of pneumonia. Coronavirus is the pathogen frequently affecting respiratory system and gastrointestinal system. There was surge in the number of cases of COVID-19 associated with the fungal rhinosinusitis, mainly by Mucormycosis and Aspergillus. This study was done to analyze and correlate various fungal etiologies in post-COVID-19 patients presenting with fungal infections and correlating histopathological findings with frozen section, KOH mount findings, and fungus culture. Aims and Objectives: (1) The aims and objectives of the study are to identify the causative fungal species in biopsy specimens of clinically suspected post-COVID-19 fungal rhinosinusitis and (2) to correlate histopathology findings with frozen section, KOH mount, and fungus culture. Materials and Methods: A prospective study conducted over a period of 4 months between May 2021 and August 2021. Total of 30 nasal biopsies were included. Patients’ data were obtained from department of pathology, Hassan Institute of Medical Sciences, Hassan. Results: Out of 30 cases, 66.67% were males and 33.33% were females with male-to-female ratio of 2:1. Majority of the cases were belonged to 41–50 years of age with mean age of 50 years. On histopathological examination, 56.67% cases were Mucor, 10% cases were mixed Mucor and Aspergillus infection. Out of 30 cases, 24 cases showed good correlation between histopathology and fungus culture. Conclusion: In our study, we found good correlation of histopathology with fungus culture findings.